SLAM-family receptors come of age as a potential molecular target in cancer immunotherapy - Farhangnia, Pooya; Ghomi, Shamim Mollazadeh; Mollazadehghomi, Shabnam; Nickho, Hamid; Akbarpour, Mahzad; Delbandi, Ali-Akbar (Frontiers in Immunology, 2023)
The signaling lymphocytic activation molecule (SLAM) family receptors were discovered in immune cells for the first time. The SLAM-family receptors are a significant player in cytotoxicity, humoral immune responses, autoimmune diseases, lymphocyte development, cell survival, and cell adhesion. There is growing evidence that SLAM-family receptors have been involved in cancer progression and heralded as a novel immune checkpoint on T cells. Previous studies have reported the role of SLAMs in tumor immunity in various cancers, including chronic lymphocytic leukemia, lymphoma, multiple myeloma, acute myeloid leukemia, hepatocellular carcinoma, head and neck squamous cell carcinoma, pancreas, lung, and melanoma. Evidence has deciphered that the SLAM-family receptors may be targeted for cancer immunotherapy. However, our understanding in this regard is not complete. This review will discuss the role of SLAM-family receptors in cancer immunotherapy. It will also provide an update on recent advances in SLAM-based targeted immunotherapies.